The NFIB/CARM1 partnership is a driver in preclinical models of small cell lung cancer - Guozhen Gao; Simone Hausmann; Natasha M. Flores; Ana Morales Benitez; Jianjun Shen; Xiaojie Yang; Maria D. Person; Sitaram Gayatri; Donghang Cheng; Yue Lu; Bin Liu; Pawel K. Mazur; et al. (Nature Communications, 2023)
Protein arginine methylation can contribute to tumor progression. Here the authors show that protein arginine methyltransferase, CARM1, methylates transcription factor NFIB to promote the growth of small cell lung cancers.